Real-world procedural and 30-day outcome using the Portico transcatheter aortic valve prosthesis: A large single center cohort. (15th February 2018) - Denegri, Andrea; Nietlispach, Fabian; Kottwitz, Jan; Suetsch, Gabor; Haager, Philipp; Rodriguez, Hector; Taramasso, Maurizio; Obeid, Slayman; Maisano, Francesco
Abstract: Background: Published procedural and short-term outcome of the Portico valve for Transcatheter Aortic Valve Implantation (TAVI) is limited. We report a single-center patient series assessing procedural and 30-day outcome of this device. Methods and results: Procedural and 30-day follow-up data were prospectively collected from a consecutive series of 73 patients (80.7 ± 6.9 years, 45% male, mean STS score: 4.8 ± 3.9) with severe aortic stenosis undergoing transcatheter aortic valve implantation (TAVI). Transfemoral access was used in 69 patients (94.5%), whereas in the remainder subclavian access was used. Concomitant interventions were performed in 30% of the patients. At 30 days, all-cause mortality and the rate of neurological events were both 2.7%. The rates of non-minor bleeding and major vascular complications were 8.2% and 4.1%, respectively. Clinically significant aortic regurgitation was limited to a single case (1.4%) of moderate regurgitation at discharge, which was reduced to mild at 30 days. Overall pacemaker rate after TAVI was 12% and the transprosthetic gradient was 6.9 ± 3.2 mm Hg. Conclusions: TAVI using the Portico system was associated with low mortality and a low rate of neurological events at 30 days and excellent hemodynamic outcome with no more than mild residual aortic regurgitation.